Role of TbFe on Perpendicular Magnetic Anisotropy and Giant Magnetoresistance Effect in [Co/Ni]N-Based Spin Valves - Tang, Minghong; Zhang, Zongzhi; Zhu, Yanyan; Ma, Bin; Jin, Qinyuan (Nano-Micro Letters, 2014)
The exchange-coupled [Co/Ni]N/TbFe nano-magnetic films can display strong perpendicular magnetic anisotropy (PMA) which depends on the Tb:Fe component ratio, TbFe layer thickness and the repetition number N of [Co/Ni]N multilayer. Perpendicular spin valves in the nano thickness scale, consisting of a [Co/Ni]3 free and a [Co/Ni]5/TbFe reference multilayer, show high giant magnetoresistance (GMR) signal of 6.5 % and a large switching field difference over 3 kOe. However, unexpected slanting of the free layer magnetization, accompanied by a reduced GMR ratio, was found to be caused by the presence of a thick Fe-rich or even a thin but Tb-rich TbFe layer. We attribute this phenomenon to the large magnetostriction effect of TbFe which probably induces strong stress acting on the free layer and hence reduces its interfacial PMA.